PENGARUH BEBAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT ACON INDONESIA GUNUNG SINDUR BOGOR - Bintang Enjelika Marpaung; Risza Putri Elburdah (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to determine the effect of workload and work motivation on employee performance at PT Acon Indonesia, Gunung Sindur, Bogor, both partially and simultaneously. The research uses a quantitative descriptive method. The sampling technique applied is a saturated sample, involving 80 respondents. Data analysis techniques include instrument testing, classical assumption tests, simple linear regression, multiple linear regression, correlation coefficient, and coefficient of determination. Hypothesis testing is conducted using t-test and F-test. The analysis results show that workload has a significant effect on employee performance, as indicated by the simple linear regression equation Y = 5.418 + 0.414X₁. The correlation coefficient is 0.742, indicating a strong relationship, and the coefficient of determination is 55.1%, meaning that performance is influenced by workload by 55.1%. This is supported by the t-test result where t-count > t-table (2.443 > 1.991) and the significance value < 0.05 (0.000 < 0.05). Work motivation also partially has a positive and significant effect on employee performance, shown by the regression equation Y = 4.679 + 0.652X₂. The correlation coefficient is 0.866, indicating a very strong relationship, and the coefficient of determination is 75%, meaning that performance is influenced by work motivation by 75%. This is confirmed by the t-test result where t-count > t-table (2.082 > 1.991) and significance value < 0.05 (0.000 < 0.05). The simultaneous test results show that workload and work motivation together have a significant effect on employee performance, as indicated by the multiple linear regression equation Y = 3.164 + 0.147X₁ + 0.212X₂. The correlation coefficient is 0.871, showing a very strong relationship, and the coefficient of determination is 75%, meaning that performance is influenced by workload and motivation by 75%. This is supported by the F-test result where F-count > F-table (9.665 > 2.723) and significance value < 0.05 (0.000 < 0.05). Therefore, H₀ is rejected and Hₐ is accepted, indicating that workload and work motivation significantly affect employee performance.